Corak Pemikiran Hermeneutika Al-Qur’an Prof. Sahiron Syamsuddin - Muhamad Ridwan Syafi'i (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to explore the hermeneutical thought patterns of the Koran; Prof. Sahiron Syamsuddin uses descriptive qualitative methods with literature analysis. The research results show that the ma'na-cum-maghza hermeneutic method developed by Prof. Sahiron Syamsuddin is a development of various previous interpretive theories with no genuinely new elements. The proposed methodology must be more thorough, and the solutions and proposals are still general and ambiguous. Criticism of classical ulama's thinking is more dominant, and the absence of the word